PENGARUH KUALITAS INFORMASI DAN KUALITAS SISTEM TERHADAP KINERJA INDIVIDU (Studi Kasus Pada PT. Bank Negara Indonesia Cabang Banyuwangi) - Sugiarto, Sugiarto; Rokhman, M. Taufiq Noor (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
Abstract Information systems as a set of interconnected components that function to collect, process, store and distribute information to support decision-making and supervision within the organization. The use of information system technology (SI) can improve user performance will be largely determined on the quality of the information system. Use of information system technology used by PT. Bank Rakyat Indonesia, Tbk one of them in 2008 issued the type of electronic channel that has been implemented for BRI customers are ATM, Phone Banking, SMS Banking, Kiosk, MiniATM and Cash Deposit Machine (CDM). PT. Bank Rakyat Indonesia, Tbk as a bank organization with a very large number and distribution of work units, makes information technology an important and decisive factor to create integration and optimize network utilization. The purpose of this research is to analyze the influence of information quality, system quality and service quality on individual performance as user of information system technology in PT. Bank Rakyat Indonesia Branch of Banyuwangi. The sample in this research is 90 employees of PT. Bank Rakyat Indonesia Branch of Banyuwangi. The results showed that the variable of information quality, system quality and service quality partially influence Bank Rakyat Indonesia, Tbk Banyuwangi Branch. While simultaneous testing Variable information quality, system quality and service quality together affect the performance of induvidual employees of PT. Bank Rakyat Indonesia, Tbk Banyuwangi Branch. Keywords: Quality of information, System quality, Service quality and individual employee performance